1995
DOI: 10.1111/j.1365-2362.1995.tb01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fractional calcium absorption and gastric emptying

Abstract: Abstract.The relationship between calcium absorption and gastric emptying and the precision of measurement of fractional calcium absorption using a single isotope technique were evaluated in 14 normal postmenopausal women (age range 61 -72 years). On two occasions separated by between 5 and 15 days, each subject was given 250mL water containing 0.2MBq of 45Ca in 20mg of calcium carrier as the chloride, 20 mg kg-I paracetamol and 9 MBq of 9 9 m T~ sulphur colloid. Venous blood samples were taken at -2, 15, 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Previous other studies on these effects have used radioisotopes or stable isotopes in clearance and other such tests. [8][9][10] We used the urinary calcium excretion as an indicator of calcium absorption. This method is based on the positive correlation between the intestinal calcium absorption and urinary calcium excretion and has often been used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous other studies on these effects have used radioisotopes or stable isotopes in clearance and other such tests. [8][9][10] We used the urinary calcium excretion as an indicator of calcium absorption. This method is based on the positive correlation between the intestinal calcium absorption and urinary calcium excretion and has often been used.…”
Section: Discussionmentioning
confidence: 99%
“…A high 44 Ca or 25 Mg ratio in the urine after digestion of the test food indicates that the absorption of the mineral was also relatively high. Unlike the double-labeling method, the single-labeling method cannot be used to measure the true absorption, but it has been shown to exhibit a high correlation with the double-labeling method (13,14), and its accuracy can be improved if the body size is included in the regression equation (15, 16); however, this method has needed ingestion of radioactive tracer. With the parallel design, it is impossible to measure the absorption of Ca or Mg using a single isotope method without adjusting by body size.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have found a significant correlation between the parameters for the rate of paracetamol absorption and scintigraphically measured gastric half-emptying time, the "gold standard" for GER measurement, 9,[12][13][14][15] but others have failed to find such correlation. 16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 99%